Multimodality Imaging in the Diagnosis, Risk Stratification and Management in the Patients with Dilated Cardiomyopathy. Practical recommendations - Lazoryshynets, V. V.; Potashev, S. V.; Fedkiv, S. V.; Rudenko, A. V.; Vitovskiy, R. M.; Rudenko, K. V.; Rudenko, S. A.; Hrubyak, L. M.; Mazur, O. A.; Chizhevskaya, O. O. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Dilated cardiomyopathy (DCM) is defined by left ventricular (LV) or biventricular dilation with systolic dysfunction in the absence of abnormal loading conditions or coronary heart disease significant enough to explain these alterations. This is a heterogeneous entity, often with a genetic background. Cardiovascular imaging is extremely important for diagnosis, prognosis and risk stratification, as well as further treatment and management guidance. Multimodality imaging approach assures the most comprehensive evaluation of all the issues related to DCM. The present paper aims to provide detailed recommendations for the use of multimodality imaging according to clinical requirements from the standpoint of modern evidence-based data and adopted to existing practice in Ukraine. Choice for one or the other imaging method should be based on the very clinical condition and individual context. “Clinically relevant” imaging techniques as well as “applicable” tools are distinguished. There are still certain gaps in the evidence base on the influence of multimodality imaging upon the management and treatment of the patients with DCM. Therefore, ongoing research is of big importance.